(untitled) (Research, Society and Development, 2021)
Objective: to investigate the nurses’ perception about the use of Nursing Care Systematization in the care provided to premature newborns, in the Intermediate Care Unit. Methodology: This is a field research, with a qualitative approach, of a descriptive character, where the data were obtained through a semi-structured interview and a questionnaire, composed of 05 open questions, carried out with 05 nurses allocated at the ICU Neonatal in a public hospital in Pará; the saturation technique was used for the answers to the questionnaire and the content analysis was based on Bardin. Result: four professionals made up the study sample, being young adults and female; most had specialization in the area, working for more than two years, contracted or tendered. It was found that the nursing care provided is aimed at performing technical procedures using protocols; the nurses’ knowledge in relation to what is the Nursing Care Systematization is consistent, however they demonstrated difficulty in differentiating it from the Nursing Process; institutional and professional barriers hinder the application of the systematization of nursing care, however they are applied in care aimed at premature newborns. Final considerations: the knowledge and understanding of the subject in question has great benefits, both for the professional and the premature newborn, and to demonstrate that the obstacles of daily nursing care cannot be greater than the need to offer assistance Of Quality.